1981
DOI: 10.1073/pnas.78.5.2712
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between glycocalicin and glycoprotein Ib of human platelets.

Abstract: Asialoglycoprotein lb and asialoglycocalicin have been isolated from the membranes and from the supernatant, respectively, after sonication of neuraminidase-treated platelets, by lectin affinity chromatography on peanut agglutinin. The isolated asialoglycoprotein lb had an apparent molecular weight of 160,000 when not reduced and 150,000 when reduced, whereas the asialoglycocalicin had an apparent molecular weight of 150,000, both reduced and unreduced, on sodium dodecyl sulfate/polyacrylamide gel electrophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…The principal sugars were found to be galactose, Nacetylglucosamine, GalNAc and sialic acid in a ratio (2:1:1:2) with serine and threonine among the most abundant amino acids. The recent studies of Clemetson et al (34) have shown that there were great similarities between the tryptic peptide maps of asialoglycocalicin and asialo-GP Iba. It appears that the site of action of the Ca2+-dependent protease that cleaves glycocalicin from GP Ib, is not too distant from the disulfides the cleavage of which separates Iba and Ib,B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The principal sugars were found to be galactose, Nacetylglucosamine, GalNAc and sialic acid in a ratio (2:1:1:2) with serine and threonine among the most abundant amino acids. The recent studies of Clemetson et al (34) have shown that there were great similarities between the tryptic peptide maps of asialoglycocalicin and asialo-GP Iba. It appears that the site of action of the Ca2+-dependent protease that cleaves glycocalicin from GP Ib, is not too distant from the disulfides the cleavage of which separates Iba and Ib,B.…”
Section: Resultsmentioning
confidence: 99%
“…The lectin, peanut agglutinin (Arachis hypogaea) has anti-T specificity (46), binding to terminal galactose residues in glycoproteins. Studies on the binding of 1251-labeled lectins to platelet membrane glycoproteins separated by SDS-PAGE have indicated that peanut agglutinin binds specifically to GP Iba when neuraminidase-treated platelets are being analyzed (34,47). These observations collectively suggest a partial similarity between the oligosaccharide chain composition of platelet GP Ib and the MN-sialoglycoprotein of erythrocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trypsinized platelet membrane was then solubilized using Triton X-114 and detergent phase was subjected to WGA-affinity chromatography ( Figure 2). Lectins have been shown to specifically recognize and bind to certain glycoproteins and this specific interaction between lectins and glycoproteins has been successfully used in the purification of platelet membrane glycoproteins (Clemetson et al, 1981, Leung et al, 1981. A combination of various immobilized lectins with different binding characteristics was revealed to be very effective for the purification of glycoproteins.…”
Section: Resultsmentioning
confidence: 99%
“…Like gpL115, GPIb and its soluble form glycocalicin (8) adhere to wheat germ lectin (7) and asialo-GPIb adheres to peanut lectin (8). GPIb (glycocalicin) consists to 60% of carbohydrate that appears to be exclusively mucin-type units linked to serine and threonine (7,42).…”
Section: Defect In Gplil5 In Lymphocytes Of Wiskott-aldrich Syndrome mentioning
confidence: 99%